Municipal self administration and local development (1993)
This article outlines a comunity's self administration and local planning experience. The place is La Mesa, capital of the province of Tequendama located in the Department of Cundinamarca. It falls under the mid-eastem planning region of the country. The object ofthis study is to reflect upon a participatory planning process. It is a social experiment giving way to important local development activities. It is undertaken in a contradictory framework: on one side, old heterogeneus schemes of municipal administration; and on the other, organizational cornmunitary efforts to satisfy everyone's needs. This effort is part of the new descentralization strategy of the Colombian State based on cornmunitary participation.